2012
DOI: 10.1128/aac.00758-12
|View full text |Cite
|
Sign up to set email alerts
|

Different Genetic Supports for the tet (S) Gene in Enterococci

Abstract: fThe diversity of tet(S) genetic contexts of 13 enterococci from human, animal, and environmental samples from different geographical areas is reported. The tet(S) gene was linked to either CTn6000 variants of chromosomal location or composite platforms flanked by IS1216 located on plasmids (ϳ40 to 115 kb). The comparative analysis of all tet(S) genetic elements available in the GenBank databases suggests that CTn6000 might be the origin of a variety of tet(S)-carrying platforms that were mobilized to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Accordingly, the present study recorded tet (M) at many sampling sites whereas tet (S), tet (A) and tet (B) were found in only limited sampling sites ( Figure 5). Further, a high detection frequency of tet (M) was recorded in this study and similar results were reported in Vietnamese shrimp and fish ponds as well (Hoa et al, 2011;Novais et al, 2012). Tetracycline contamination in aquaculture environment 14 The tet (M) gene has been detected at high percentages in bacteria which w aquaculture sites in Korea and Japan (Kim et al, 2004) Similarly, this study als in many isolated resistant bacteria strains (Table 3).…”
Section: Pcr Detection Of Args In Water Samplessupporting
confidence: 84%
“…Accordingly, the present study recorded tet (M) at many sampling sites whereas tet (S), tet (A) and tet (B) were found in only limited sampling sites ( Figure 5). Further, a high detection frequency of tet (M) was recorded in this study and similar results were reported in Vietnamese shrimp and fish ponds as well (Hoa et al, 2011;Novais et al, 2012). Tetracycline contamination in aquaculture environment 14 The tet (M) gene has been detected at high percentages in bacteria which w aquaculture sites in Korea and Japan (Kim et al, 2004) Similarly, this study als in many isolated resistant bacteria strains (Table 3).…”
Section: Pcr Detection Of Args In Water Samplessupporting
confidence: 84%
“…The F type harboured IS Efm2 , representative of the IS 256 family. Thus far, in enterococci this IS has been solely observed inserted between orf13 and tetS within CTn 6000 transposon [43]. In our study, we report for the first time the insertion of IS Efm2 into Tn 1546 .…”
Section: Discussionmentioning
confidence: 50%
“…that carry multidrug-resistant determinants have been shown to be transferable to E.coli from A.salmonicida, A.hydrophila, V.cholerae, Shigella species, Salmonella species and E.coli (Suzuki et al 2008;Sorum 2006). Genes coding for tetracycline resistance in fish farm bacteria and human clinical isolates in Japan has shown high similarity, suggesting that they were derived from the same source (Novais et al 2012;Vincent et al 2015). Furthermore, in laboratory experiments, transfer of tetracycline resistance from marine strains of Photobacterium species, Vibrio species, Aeromonas species and Pseudomonas species into E.coli by conjugation was recorded suggesting that transfer of resistance gene from marine bacteria to bacteria associated with the human gut is possible.…”
Section: Plasmidsmentioning
confidence: 98%
“…The spread to humans can happen through direct contact with water or aquatic organisms, through drinking water, through handling or consumption of aquaculture products (Suzuki et al 2008). Direct spread from aquatic environments to humans can be involved human pathogens, such as V. cholera, V. vulnificus, Shigella species and Salmonella species or opportunistic pathogens, such as A. hydrophila, P. shigelloides, E. tarda and E. coli (Novais et al 2012;Vincent et al 2015). Thus, the occurrence of antimicrobial-resistant Salmonella species in aquatic environments is most likely attributable to contamination from human, animal or agriculture environments.…”
Section: Direct Spread Of Antibiotic Resistancementioning
confidence: 99%